Dynamics and spectroscopy of van der Waals complexes composed of ammonia and noble gases - Sette, Camila D’Avila Braga (2021)
In this work, we calculate the rovibrational energies and spectroscopic constants for the systems formed by ammonia (NH3) and noble gases (Ng=He, Ne, Ar, Kr and Xe). For the spectroscopic constant calculations, we used two different methods: Dunham and another one that use rovibrational energies (here calculated by discrete variable method). In both cases, we used the improved Lennard–Jones potential energy curves (PECs). These PECs, which describe very well van der Waals systems, were built using the dissociation and equilibrium distance obtained from experiments of crossed molecular beams. The spectroscopic constant results, obtained by both methods were in excellent agreement with each other for all NH3-Ng studied systems. Also in relation to NH3-He system, we realize that although this system has a relatively small dissociation energy, it has one vibrational level. Finally, the spectroscopic constants and fundamental rovibrational energy results were used to verify the stability of each system through the lifetime decomposition.